A Special Class of Harmonic Univalent Functions - Gencel, Tuğba; Yalçin , Sibel (Sarajevo Journal of Mathematics, 2024)
We define and investigate a special class of Salagean-type harmonic univalent functions in the open unit disk. We obtain coefficient conditions, extreme points, distortion bounds, convex combinations for the above class of harmonic univalent functions. 2000 Mathematics Subject Classification. Primary 30C45 ; Secondary 30C50